The intellectual foundations of Chinese modernity : cultural and political thought in the Republican era - Fung, Edmund S. K. (Cambridge University Press, 2010)
"This book is the first attempt to present an integrated overview of the development of liberal, conservative, and socialist thought in the Republican era, which formed the intellectual foundations of Chinese modernity. The book explores ideas in relation to their cultural and political backgrounds. The author argues that the key to understanding the Chinese quest for modernity lies in an appreciation of the interrelatedness and interplay of different schools of thought. There is no one single vision of Chinese modernity. Instead, different visions contest, interact, and influence one another"--Provided by publisher